Hipervolemia dan Keletihan pada Pasien Chronic Kidney Disease Stage 5: Sebuah Studi Kasus - Sari, Yuyun Kartika; Sari, Eka Afrima; Pratiwi, Sri Hartati (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Chronic kidney disease leads to a progressive decline in kidney function. A decrease in kidney function leads to water and sodium retention, which subsequently causes hypervolemia. Mr. N came with complaints of shortness of breath to the hospital; the patient has undergone hemodialysis five times. In the process of examination, the presence of peripheral edema, pulmonary edema, and shortness of breath was found to be characterized by rapid and shallow breathing. According to the case, there was a problem of hypervolemia and fatigue in Mr. N. The aim of this study is to explore the application of nursing care in patients with chronic kidney disease stage 5 with hyperbolemia and fatigue. The method used is a case study descriptive of nursing care provision systematically starting from the examination, determination of diagnosis, planning, implementation, and evaluation of nurse care. The course was carried out for three days in a collaborative and independent manner. General interventions performed include hypervolemia management consisting of fluid restriction; edema and jugular venous pressure monitoring; interdialytic weight gain calculation; fluid intake and output control; monitoring of urea and creatinine levels; as well as co-administration of furosemide and hemodialysis. General interventions to overcome fatigue performed by giving semi-fowler positions; deep breathing relaxation; oxygen therapy; transfusion packed red cells, and relaxation foot massage. After the evaluation results were obtained for the problem of hypervolemia showed a decrease in the level of edema in the leg from degree 2 to degree 1, decreased jugular venous pressure, reduced blood pressure, interdialytic weight gain of 3.2%, improvement in the values of urea and creatinine, and a glomerular filtration rate post-hemodialysis of 8.28 ml/min/1.73 m2. As for the problem of fatigue, fatigue decreased from a score of 35 to 29, sickness decreased from a scale of 4 to 3, and breathing frequency was within the normal boundaries, so it can be concluded that the problems of nursing hyperbolemia and fatigue are partially overcome. Keywords: Chronic Kidney Disease, Hypervolemia, Fatigue  ABSTRAK Chronic Kidney Disease mengakibatkan penurunan fungsi ginjal secara progresif. Penurunan fungsi ginjal mengakibatkan retensi air dan natrium yang selanjutnya menimbulkan hipervolemia. Tn.N datang dengan keluhan sesak nafas ke RS, pasien telah menjalani hemodialisis sebanyak 5 kali. Pada proses pengkajian ditemukan adanya edema perifer, edema paru, serta sesak nafas yang ditandai pernafasan cepat dan dangkal. Berdasarkan kasus ditemukan adanya masalah hipervolemia dan keletihan pada Tn.N. Tujuan penelitian ini untuk mengekplorasi penerapan asuhan keperawatan pada pasien chronic kidney disease stage 5 dengan masalah keperawatan hipervolemia dan keletihan. Metode yang digunakan yaitu dengan studi kasus deskriptif pemberian asuhan keperawatan secara sistematis diawali dari pengkajian, penentuan diagnosa, perencanaan, implementasi, dan evaluasi keperawatan. Intervensi dilakukan selama 3 hari secara kolaborasi dan mandiri. Intervensi generalis dilakukan meliputi manajemen hipervolemia yang terdiri atas pembatasan cairan, pemantauan edema dan jugular venous pressure, perhitungan interdialytic weight gain, pemantauan intake dan output cairan, pemantauan kadar ureum dan kreatinin, serta kolaborasi pemberian furosemide, dan tindakan hemodialisis. Adapun intervensi generalis untuk mengatasi keletihan dilakukan dengan pemberian posisi semi fowler, relaksasi nafas dalam, terapi oksigen, transfusi packed red cells, dan relaksasi pijat kaki. Setelah dilakukan evaluasi didapatkan hasil untuk masalah hipervolemia, terdapat penurunan tingkat edema pada kaki dari derajat 2 menjadi derajat 1, penurunan jugular venous pressure, penurunan tekanan darah, interdialytic weight gain 3,2%, perbaikan pada nilai ureum dan kreatinin dengan glomerular filtration rate post-hemodialisis 8,28 ml/min/1,73m2. Adapun untuk masalah keletihan, kelelahan berkurang dari skor 35 menjadi 29, sesak berkurang dari skala 4 menjadi 3, frekuensi nafas dalam batas normal, sehingga dapat disimpulkan masalah keperawatan hipervolemia dan keletihan teratasi sebagian. Kata Kunci: Chronic Kidney Disease, Hipervolemia, Keletihan